Mapping and characterization of antigenic epitopes of arginine kinase of Scylla paramamosain. Issue 2 (June 2015) - Yang, Yang; Cao, Min-Jie; Alcocer, Marcos; Liu, Qing-Mei; Fei, Dan-Xia; Mao, Hai-Yan; Liu, Guang-Ming
Highlights: The conformational epitopes and their key amino acid from Scylla paramamosain AK were identified. The linear epitopes of AK were mapped using the synthesized overlapping peptides and confirmed by cell model. The predominant epitope type of AK was defined and chemical bonds essential for the allergenicity of AK was clarified. Abstract: Arginine kinase (AK) is a panallergen present in crustaceans, which can induce an immunoglobulin (Ig) E-mediated immune response in humans. The aim of this work was to map and characterize the antigenic epitopes of Scylla paramamosain AK. Specific-protein-A-enriched IgG raised in rabbits against purified S. paramamosain AK was used to screen a phage display random peptide library. Five AK mimotope clones were identified among 20 random clones after biopanning. Four conformational epitopes D3 A4 K43 M1 A5 T49 T44 I7, L31 K33 V35 T32 E11 E18 F14 S34 D37, V177 G172 M173 D176 Q178 T174 L181 K175 L187, and R202 L170 Y203 E190 P205 W204 L187 T206 Y145 were identified with the program LocaPep, and mapped to S. paramamosain AK. The key amino acids of these conformational epitopes were D3, K33, T174, and W204, respectively. On the basis of biopanning, six IgE-specific peptides were mapped with synthetic overlapping peptides using the sera from crab-allergic patients, and four seropositive peptides (amino acids 113–127, 127–141, 141–155, and 204–218) were confirmed as linear epitopes in a degranulation assay in RBL-2H3 cells. Stability experiments showed that the structural integrity of AK is essential for its allergenicity, and the intramolecular disulfide bond at Cys201 –Cys271 is essential for its structural stability.